(untitled) (Research, Society and Development, 2020)
The main objective of the study was to portray how the managers of the rural properties work the family succession. As for the problem, was it sought to understand how the managers of rural properties work on family succession? In the methodological part, the deductive, qualitative and quantitative approach methods were used. The procedures were descriptive, field research and comparative. For data collection, observation, interview, questionnaire, bibliographic research and documentary research were used. For data analysis, the electronic spreadsheet and content analysis were adopted. As for the sample of properties, there was accessibility. The theoretical basis is composed of previous studies and topics related to the study. Through the bibliographic material, the elements that characterize the family succession and the characteristics of the properties by the size criterion were sought. The research was applied in 18 rural properties in the municipality of Alegria - RS and 16 in the municipality of Coronel Bicaco - RS. Through research applied to parents and the questionnaire applied to children aged 15 and over, it was noticed that 44.12% of families have not yet thought about the possibility of a successor taking over the property. It was found that 52.94% do not carry out any activity aimed at the succession process. Thus, it was discovered that it is extremely important for rural families to have knowledge regarding family succession in their properties, because with the lack of the succession process, what we call a rupture of the family business may occur, and planning it it will bring advantages even for the continuity of family work.